Kajian Tingkat Kematangan Gonad Rajungan Portunus pelagicus Betina Yang Ditangkap Melalui Bubu di Candi Pamekasan, Jawa Timur - Mulyani, Rahma; Maryani, Leni; Sundoko, Ahmad; Wihardi, Yedi; Yusanti, Indah Anggraini; Pangentasari, Dwinda; Septinar, Helfa (Universitas Batangahari Jambi, 2025)
The blue swimming crab (Portunus pelagicus) is a high-value fishery commodity in Indonesia and plays a vital role in supporting the livelihood of coastal communities. The reproductive aspect, particularly the gonadal maturity stage (GMS) of the blue swimming crab, serves as a key indicator in describing spawning readiness. Furthermore, observations of GMS provide insights into spawning patterns and the size at first maturity, which are essential parameters for biologically based fisheries management. This study aimed to examine the gonad maturity stages (GMS) of female P. pelagicus caught using collapsible traps (bubu) in the coastal waters of Candi, Pamekasan, Madura. Sampling was conducted from August to December 2024 using a random sampling method from local fishers’ catches. The gonad maturity stages were determined visually based on APRI (2020) guidelines, classifying female crabs into three stages: GMS I (immature), GMS II (developing), and GMS III (mature or ovigerous). A total of 1,559 individuals were analyzed, showing a strong dominance of GMS II (96.86%), followed by GMS I (1.09%) and GMS III (2.05%). The highest proportion of GMS III occurred in October (2.97%) and the lowest in November (1.04%). The dominance of GMS II indicates that most of the captured crabs were in the gonad development phase toward maturity. The low proportion of GMS III suggests that the observation period (August–December) was not the main spawning season in the study area. Temporal variation in GMS distribution is likely influenced by environmental factors such as seasonal changes, habitat type, food availability, and fishing pressure. These findings provide essential reproductive biological data that can support the sustainable management of blue swimming crab fisheries in the Pamekasan waters.